Karakteristik Pertanggungjawaban Kepala Daerah Dalam Penyelenggaraan Pemerintahan Daerah Menurut Sistem Pemerintahan Presidensial - Amiq, Bachrul (UI Scholars Hub, 2020)
Since the beginning of the formation of the constitution for an independent Indonesia by the founders of the state, the state government system adopted is a presidential system. After the amendment to the 1945 Constitution, the perpetrators of the changes, namely the Peoples Consultative Assembly (MPR) wanted to emphasize that the 1945 Constitution of the Republic of Indonesia adhered to a pure presidential system by upholding the supremacy of the constitution, so that the executive as government administrator was responsible to the constitution. This must be in line with the implementation of local government. However, it is not explained what the accountability model looks like. In this article, what is the basis of accountability as one of the characters that must exist in a presidential system of government and what is the model of accountability in a presidential system of government that distinguishes it from the character of accountability in a parliamentary system of government? Based on the problems raised, this type of research is normative legal research, namely by only examining legal materials. While the approach model here only uses two approaches, namely the statutory approach and the conceptual approach.